Fresche fontanis : studies in the culture of medieval and early modern Scotland - Hadley Williams, Janet; McClure, J. Derrick (Cambridge Scholars, 2013)
Fresche fontanis contains twenty-five studies presenting major new research by leading scholars in Scottish culture of the late fourteenth and fifteenth, sixteenth, and seventeenth centuries. The three-part collection includes essays on the prominent writers of the period: James I, Robert Henryson, William Dunbar, John Bellenden, David Lyndsay, John Stewart of Baldynneis, William Fowler, Alexander Montgomerie, Andrew Melville and Alexander Craig. There are also essays on the Scottish romances ...